2021
DOI: 10.1155/2021/6641055
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Exerts Anti-Inflammatory, Antioxidant, and Neuromodulatory Effects That Could Potentially Be Useful in the Treatment of Vertigo

Abstract: The acute phase of vertigo involves multiple neurotransmitters, inflammatory mediators, and products of oxidative stress. The vestibular pathway has multiple melatonin receptors distributed along its path, both centrally and peripherally. In addition, melatonin has been shown to be a powerful antioxidant and anti-inflammatory agent against factors related to vertigo, such as Bax/caspases, interleukins, and chemokines. Likewise, it exerts central GABAergic, antidopaminergic, and anti-migraine functions and regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…This therapeutic displays anti-tumoral properties, regulating cell cycle progression, apoptosis, induced-oxidative stress, immune stimulation, and growth signaling, exerting anti-proliferative effects [ 80 , 81 ]. It was shown that melatonin represses the Warburg effect, ameliorates disturbed mitochondrial bioenergetics, and is a pro-oxidant in cancer cells, even in cancer stem cells (CSCs) [ 82 , 83 ].…”
Section: Therapeutics Treatments In Ebv- and -Kshv-infected Malignanciesmentioning
confidence: 99%
“…This therapeutic displays anti-tumoral properties, regulating cell cycle progression, apoptosis, induced-oxidative stress, immune stimulation, and growth signaling, exerting anti-proliferative effects [ 80 , 81 ]. It was shown that melatonin represses the Warburg effect, ameliorates disturbed mitochondrial bioenergetics, and is a pro-oxidant in cancer cells, even in cancer stem cells (CSCs) [ 82 , 83 ].…”
Section: Therapeutics Treatments In Ebv- and -Kshv-infected Malignanciesmentioning
confidence: 99%